A cross-sectional study of the prevalence and associations of iron deficiency in a cohort of patients with chronic obstructive pulmonary disease. Issue 7 (6th July 2015) - Nickol, Annabel H; Frise, Matthew C; Cheng, Hung-Yuan; McGahey, Anne; McFadyen, Bethan M; Harris-Wright, Tara; Bart, Nicole K; Curtis, M Kate; Khandwala, Shivani; O'Neill, David P; Pollard, Karen A; Hardinge, F Maxine; et al.
Abstract : Objectives: Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality. Iron deficiency, with or without anaemia, is associated with other chronic conditions, such as congestive heart failure, where it predicts a worse outcome. However, the prevalence of iron deficiency in COPD is unknown. This observational study aimed to determine the prevalence of iron deficiency in COPD and associations with differences in clinical phenotype. Setting: University hospital outpatient clinic. Participants: 113 adult patients (65% male) with COPD diagnosed according to GOLD criteria (forced expiratory volume in 1 s (FEV1 ): forced vital capacity (FVC) ratio <0·70 and FEV1 <80% predicted); with age-matched and sex-matched control group consisting of 57 healthy individuals. Main outcome measures: Prevalence of iron deficiency, defined as: any one or more of (1) soluble transferrin receptor >28.1 nmol/L; (2) transferrin saturation <16% and (3) ferritin <12 µg/L. Severity of hypoxaemia, including resting peripheral arterial oxygen saturation (SpO2 ) and nocturnal oximetry; C reactive protein (CRP); FEV1 ; self-reported exacerbation rate and Shuttle Walk Test performance. Results: Iron deficiency was more common in patients with COPD (18%) compared with controls (5%). In the COPD cohort, CRP was higher in patients with iron deficiency (median 10.5 vs 4.0 mg/L, p<0.001), who were also more hypoxaemic than their iron-replete counterparts (median resting SpO2 92% vs 95%, p<0.001), but haemoglobin concentration did not differ. Patients with iron deficiency had more self-reported exacerbations and a trend towards worse exercise tolerance. Conclusions: Non-anaemic iron deficiency is common in COPD and appears to be driven by inflammation. Iron deficiency associates with hypoxaemia, an excess of exacerbations and, possibly, worse exercise tolerance, all markers of poor prognosis. Given that it has been shown to be beneficial in other chronic diseases, intravenous iron therapy should be explored as a novel therapeutic option in COPD.